2010
DOI: 10.1002/adem.200980070
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Material Surfaces Generated by Plasma Polymerized Allylamine Enhance Vinculin Mobility in Vital Human Osteoblastss

Abstract: Several studies suggest that the modification of an implant surface by chemical means plays an important role in bone tissue engineering. Previously we have shown that osteoblast cell adhesion and spreading can strongly be increased by a positively charged surface. Cell adhesion and migration are two vital processes that are completely dependent on coordinated formation of focal adhesions. Changes in the organization of the actin cytoskeleton and the focal adhesions are essential for numerous cellular processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 41 publications
4
46
0
Order By: Relevance
“…Such a layer stimulated the mobility of vinculin containing focal adhesion contacts [55]. Other techniques, like self assembled monolayers of alkanethiols, silanisation, radiation grafting are also applied to generate chemical groups onto a material surface, including amino, methyl, hydroxyl, ether, carbonyl, carboxyl and carbonate [56][57][58].…”
Section: Cell Regulation By Chemical Characteristics Of a Materialsmentioning
confidence: 99%
“…Such a layer stimulated the mobility of vinculin containing focal adhesion contacts [55]. Other techniques, like self assembled monolayers of alkanethiols, silanisation, radiation grafting are also applied to generate chemical groups onto a material surface, including amino, methyl, hydroxyl, ether, carbonyl, carboxyl and carbonate [56][57][58].…”
Section: Cell Regulation By Chemical Characteristics Of a Materialsmentioning
confidence: 99%
“…Cells get a growth advantage due to this very early strong adhesion. Although these plasma-based surfaces are non-protein coated surfaces without any ligands for integrin receptors cell's development is pushed as lot of our experiments could demonstrate: the spreading was increased, the formation of adhesion components (paxillin, vinculin) was pronounced Nebe et al, 2007) and an increase in long term adhesion of living cells could be observed, accompanied by enhanced cell migration (Rebl et al, 2010a;Rebl et al 2010b). The cell physiology of cells on plasma polymerized allylamine is altered in a positive manner -signalling molecules in the downstream signal cascade become stimulated intracellularly or are faster in their phosphorylation process (Fig.…”
Section: Improvement Of Osteoblast Adhesion: Comparision Of a Plasma mentioning
confidence: 80%
“…Note that already after 2 min cell adhesion is impressively improved on PPAAm which is significant, but not for cell adhesion on COL (details see Nebe et al, 2007). Human MG-63 cells, adherent cells related to Ti_P=1, flow cytometric approach, T-test paired, *p<0.01. experiments can be found elsewhere Nebe et al, 2007;Rebl et al, 2010a). Furthermore, covalent coupling reactions of the plasma generated amino groups with collagen I (COL) were carried out to compare the cell adhesion between solely surface charges received by PPAAm and additionally immobilized COL. For the immobilization of collagen I the bifunctional spacer polyethylene glycol diacid (PEG DA) catalyzed by carbodiimide, was used.…”
Section: Improvement Of Osteoblast Adhesion: Comparision Of a Plasma mentioning
confidence: 99%
“…A treatment of Titanium samples with a comparable process called plasma-polymerized allylamine, based on the polymerization of allylamine after activation with a continuous wave oxygen-plasma, creates a positively charged amino group rich surface aimed at improving attachment of the negatively charged matrix substance hyaluronan. This coating was found to be advantageous concerning initial osteoblast adhesion and spreading and to have beneficial effects in vitro on the formation of focal adhesions as well as on cell morphology and spreading and vinculin mobility (Rebl et al, 2010) of osteoblasts. An in vivo examination in rats revealed no negative influence on the number of total and tissue macrophages, T cells and MHC class II antigen-presenting cells in the peri-implant tissue (Hoene et al, 2010).…”
Section: Creation Of Bioactive Surfacesmentioning
confidence: 98%